Without an equality sign and not knowing the plus or minus values of the given terms it can't be considered to be an equation.
There are no real solutions to this equation because you cannot take the square root of a negative number. However,x2 + 4 = 0x2 = -4sqrt(x2) = sqrt(-4)x = 2i, -2ihere are the imaginary solutions.
x2 + 3x + 3 = 0 doesn't factor neatly. Applying the quadratic formula we find two imaginary solutions: (-3 plus or minus the square root of -3) divided by 2x = -1.5 + 0.8660254037844386ix = -1.5 - 0.8660254037844386iwhere i is the square root of negative 1
Using the quadratic equation formula: x = -3 - the square root of 3 or x = -3 + the square root of 3
-2
4
There are no real solutions to this equation because you cannot take the square root of a negative number. However,x2 + 4 = 0x2 = -4sqrt(x2) = sqrt(-4)x = 2i, -2ihere are the imaginary solutions.
Yes. For example, the equation x2 = 2, which in standard form is x2 - 2 = 0, has the two solutions x = square root of 2, and x = minus square root of 2.
x2 + 3x + 3 = 0 doesn't factor neatly. Applying the quadratic formula we find two imaginary solutions: (-3 plus or minus the square root of -3) divided by 2x = -1.5 + 0.8660254037844386ix = -1.5 - 0.8660254037844386iwhere i is the square root of negative 1
x2 + 3x - 18 = 0 (x - 3)(x + 6) = 0 x = 3 or -6
Using the quadratic equation formula: x = -3 - the square root of 3 or x = -3 + the square root of 3
X2+11x+11 = 7x+9 X2+11x-7x+11-9 = 0 x2+4x+2 = 0 Solve as a quadratic equation by using the quadratic equation formula or by completing the square: x = -2 + or - the square root of 2
x^2 + 3x +7 = 0 doesn't factor neatly. Applying the quadratic equation, we find two imaginary solutions: (-3 plus or minus the square root of -19) divided by 2x = -1.5 + 2.179449471770337ix = -1.5 - 2.179449471770337iwhere i is the square root of negative 1
It is the equation inside the square root of the Quadratic FormulaIf > 0 there is a solutionIf < 0 there is no solutionBecause you can not calculate the Square Root of a Negative Number
-2
4
x2 - 2x - 15 = 0
x2-10 = 0 x2 = 10 x = the square root of 10